Universal spectral signatures in pnictides and cuprates: the role of quasiparticle-pair coupling. (3rd October 2017) - Sacks, William; Mauger, Alain; Noat, Yves
Abstract: Understanding the physical properties of a large variety of high- T c superconductors (SC), the cuprate family as well as the more recent iron-based superconductors, is still a major challenge. In particular, these materials exhibit the 'peak-dip-hump' structure in the quasiparticle density of states (DOS). The origin of this structure is explained within our pair–pair interaction (PPI) model: The non-superconducting state consists of incoherent pairs, a 'Cooper-pair glass' which, due to the PPI, undergoes a Bose-like condensation below T c to the coherent SC state. We derive the equations of motion for the quasiparticle operators showing that the DOS 'peak-dip-hump' is caused by the coupling between quasiparticles and excited pair states, or 'super-quasiparticles'. The renormalized SC gap function becomes energy-dependent and non retarded, reproducing accurately the experimental spectra of both pnictides and cuprates, despite the large difference in gap value.